Metabolic syndrome and quality of life: a systematic review - Patrícia Pozas Saboya; Luiz Carlos Bodanese; Paulo Roberto Zimmermann; Andréia da Silva Gustavo; Caroline Melo Assumpção; Fernanda Londero
ABSTRACT Objectives: to present currently available evidence to verify the association between metabolic syndrome and quality of life. Method: Cochrane Library, EMBASE, Medline and LILACS databases were studied for all studies investigating the association with metabolic syndrome and quality of life. Two blinded reviewers extracted data and one more was chosen in case of doubt. Results: a total of 30 studies were included, considering inclusion and exclusion criteria, which involved 62.063 patients. Almost all studies suggested that metabolic syndrome is significantly associated with impaired quality of life. Some, however, found association only in women, or only if associated with depression or Body Mass Index. Merely one study did not find association after adjusted for confounding factors. Conclusion: although there are a few studies available about the relationship between metabolic syndrome and quality of life, a growing body of evidence has shown significant association between metabolic syndrome and the worsening of quality of life. However, it is necessary to carry out further longitudinal studies to confirm this association and verify whether this relationship is linear, or only an association factor.